Residential Location and Youth Unemployment: The Economic Geography of School-To-Work Transitions - Regina T. Riphahn (Institute for the Study of Labor (IZA), 1999)
In response to increased international policy attention to youth unemployment this study investigates post-secondary school transitions of school leavers. Multinomial logit models are estimated for male and female German youth. The models control for individual, parent, and household characteristics, for those of the youth?s region of residence and local labor markets. The findings suggest that immigrant youth has particularly low participation rates in continued education, and that youth unemployment is centered in high unemployment states and metropolitan areas. Recent changes in academic benefit policies do not seem to be correlated with changes in academic enrollment, whereas men?s transitions to the military do reflect recent changes in defense policies.
Keywords: J68; J64; J24; 330; School-to-Work; youth unemployment; local labor markets; Absolventen; Jugendarbeitslosigkeit; Jugendliche Arbeitskräfte; Regionaler Arbeitsmarkt; Geschlecht; Ausländer; Schätzung; Deutschland